Methodical instructions to perform laboratory work in the course "Hydraulics, hydraulic and pneumatic drives" - Rogovyi, Andrii; Krupa, Evgeniy Sergeevich; Rezvaya, Kseniya Sergeevna (Національний технічний університет "Харківський політехнічний інститут", 2025)
Purpose of work - study of devices for measuring pressure in the liquid, verification of technical manometer with a tubular spring and determine the accuracy of pressure measurement manometer.
Keywords: methodical instructions; laboratory work; practical classes; hydraulics; hydraulic drives; pneumatic drives; sectoral engineering